2020
DOI: 10.1093/jac/dkaa476
|View full text |Cite
|
Sign up to set email alerts
|

Two-dose emtricitabine/tenofovir alafenamide plus bictegravir prophylaxis protects macaques against SHIV infection

Abstract: Objectives Current prophylaxis options for people at risk for HIV infection include two US FDA-approved daily pre-exposure prophylaxis (PrEP) regimens and guidelines for a 2-1-1 event-driven course specifically for men who have sex with men. Despite this, PrEP use rates remain suboptimal, and additional PrEP options may help to improve uptake among diverse populations. Here, we evaluated protective efficacy of two-dose PrEP and two-dose postexposure prophylaxis (PEP) schedules with emtricitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…[13][14][15] Simian retroviral challenge studies have found that a single pre-exposure and single postexposure dose of this combination was highly protective. 16 The current study found this regimen to be safe and well-tolerated with the best completion rates (over 90%) of any PEP regimen studied at our center. Although PEP-associated side effects of nausea/vomiting, diarrhea/loose stool, fatigue, and headache were occasionally noted, they were generally mild, and were less common than previously studied PEP regimens.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…[13][14][15] Simian retroviral challenge studies have found that a single pre-exposure and single postexposure dose of this combination was highly protective. 16 The current study found this regimen to be safe and well-tolerated with the best completion rates (over 90%) of any PEP regimen studied at our center. Although PEP-associated side effects of nausea/vomiting, diarrhea/loose stool, fatigue, and headache were occasionally noted, they were generally mild, and were less common than previously studied PEP regimens.…”
Section: Discussionmentioning
confidence: 54%
“…Given that 2 of the 3 drugs used in oral PrEP regimens are present in BIC/FTC/TAF, it is reasonable to presume that people who tolerate the 3-drug regimen could readily transition to the 2-drug regimen for chronic PrEP. Given that simian studies suggest that BIC/FTC/TAF was protective when given as event-driven PEP/PrEP (ie, one dose before and after a retroviral challenge), 16 it is also possible that this combination could become used as an on-demand PrEP regimen; but, this approach would require human studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Given the timing of HIV DNA integration after reverse transcription, it has been hypothesized that adding an INSTI to an NRTI regimen for 2-1-1 PrEP may increase the window of prevention. 30 This was explored in a SHIV macaque study of two-dose, event-driven therapy. 30 When administered 2 hours before and 24 hours after, emtricitabine/TAF (F/TAF) and bictegravir 25 mg prevented 100% (6/6) of SHIV seroconversion but this was similar to F/TAF alone (5/6, 83%, 95.2% per-exposure risk reduction).…”
Section: Treatment-experiencedmentioning
confidence: 99%
“…[ 34 ▪▪ ]. A second study with two oral doses of emtricitabine, tenofovir alafenamide and bictegravir found complete protection against rectal SHIV infection when the doses were administered 2 h before and 24 h post challenge, and 82%–90% efficacy when the two dose regimen was initiated within 24 h after exposure [ 35 ▪ ]. These two macaque studies document biological efficacy of a “before or after sex” HIV prevention pill that may better adapt to different needs among PrEP and PEP users.…”
Section: Preexposure Prophylaxis Testing Using the Repeat Low Dose Ma...mentioning
confidence: 99%